Pengaruh Lingkungan, Motivasi dan Kemandirian Belajar Terhadap Hasil Belajar Siswa SMK Konsentrasi Teknik Instalasi Tenaga Listrik di Kota Serang - Eka Kusuma, Dias; Fatkhurrokhman, Mohammad; Desmira (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research is a quantitative study which aims to find the influence of the learning environment, learning motivation and learning independence on the learning outcomes of TITL concentration vocational school students in Serang City. The method used is quantitative with an Ex Post Facto approach. The population in this study was 409 students at the TITL concentration vocational school in the city of Serang, and the sample used was 202 students, with data collection techniques using questionnaires and documentation. The results of the research are (1) there is a negative and significant influence of the learning environment (X1) on learning outcomes (Y) of 3.9%, (2) there is a negative and significant influence of learning motivation (X2) on learning outcomes (Y) of 10, 3%, (3) there is a negative and significant influence of learning independence (X3) on learning outcomes (Y) of 3.9%, (4) there is a simultaneous and significant influence of the learning environment (X1) and learning motivation (X2) on learning outcomes (Y) is 27.2%, (5) there is a simultaneous and significant influence of learning motivation (X2) and learning independence (X3) on learning outcomes (Y) of 10.8%, (6) there is a simultaneous and significant influence of the learning environment (X1) and learning independence (X3) on learning outcomes (Y) of 10.6%, (7) there is a simultaneous and significant influence of the learning environment (X1), learning motivation (X2) and learning independence (X3) on learning outcomes ( Y) of 28.8%. So it can be concluded that the learning environment, learning motivation and learning independence have an influence on the learning outcomes of TITL concentration vocational school students in the city of Serang.